A case study in three species ecological ammensalism - Rama Mohan, P; Acharyulu, K.V.L.N; Prasanna Anjaneyulu, P (Journal of Experimental Sciences, 2012)
In this paper, A case in three species ecosystem is investigated numerically.This system is formed by a set of three first order non-linear simultaneous equations in N1, N2 and N3.The relations among the natural growth rate of enemy species and the dominance reversal time between predator and enemy are established. In addition to it, the interactions among the three species are also discussed .Some observations are presented by Numerical study. AMS Classification: 92 D 25, 92 D 40